Education as a Means of Jariyah Charity: An Analysis of the Hadith on Post-Death Charity from the Perspective of Islamic Education - Baiq Hadi Nurmala Yuni; Mohammad Fattah (Al-Alim: Jurnal Pendidikan Agama Islam, 2026)
Education is a conscious and systematic effort to create an environment and learning process that allows students to play an active role in developing their potential. This study uses a library research approach and is a qualitative research type. Primary data were obtained from the main books of hadith and hadith commentary, while secondary data came from books and supporting literature, such as language dictionaries and various scientific works discussing the types of ongoing charity. The data analysis technique used is content analysis, which is an effort to examine and thoroughly examine written or printed information objectively and systematically to uncover the messages contained therein. Belief in life after death is one of the fundamental teachings of Islam. Ongoing charity encompasses all forms of good deeds that provide broad benefits to others, both material and non-material. Forms of material charity include the construction of hospitals, schools, mosques, and other public facilities. Education is an important means of realizing ongoing charity as explained in the hadith regarding charity after death. Through education, the knowledge taught and practiced continues to provide ongoing benefits and rewards, both through the learning process and written works. This confirms that education in Islam is not only oriented towards worldly knowledge, but also becomes a medium for the formation of good deeds that have a spiritual dimension and have long-term value.